Public Participation in Religious Political Discourse in the 2019 Indonesia Presidential Election - Mega Hidayati; Tito Handoko (IAIN Ponorogo, 2022)
Recently, religious politics seems to be a trend in the public which is considered to have a significant impact on people's political choices on the democracy momentum. This research attempted to examine the relationship between religious political discourse and public participation in national political contestation in order to explain the relationship between public participation in religious political discourse in the 2019 Presidential Election. This research used an exploratory-oriented qualitative research method to analyze research problems from reading sources by applying content analysis. This research found that religious political discourse had dominated the 2019 presidential election as used by two pairs of candidates, Jokowi-Ma'ruf and Prabowo-Sandi in their religious narratives and symbols on the stage of the 2019 presidential election which then also influenced the increase in the number of voters participating in the 2019 presidential election, although it was not a major factor in attracting voters. Both Jokowi and Prabowo had always realized that highlighting the religious aspect followed by the implementation of the right political strategy had increased their chances of winning and increased public participation in the 2019 presidential election.